La politisation des contestations écologistes contre les activités de croisière maritime - Nathan Gouin (L'Espace Politique)
For some years now, European port cities have been abuzz with new protests against cruise activities. Limited to Venice until 2019, these protests have since spread to many cities, firstly in the Mediterranean (Barcelona, Palma de Mallorca, but also Marseille, Ajaccio and Nice), and then elsewhere in Europe. These protests are part of a wider shift in the balance of power between ideologies and a growing emphasis on political ecology. The economic and tourism model of port cities, based on neo-liberal growth, is being increasingly challenged by various forms of politicisation. The example of the cruise industry shows that there is a renewal of conflict within port cities, with some elected representatives breaking with liberal corporatism, and a new generation of environmental activists. The aim of the article, which is part of the literature on port development conflicts, is to identify and characterise these forms of politicisation through an analysis based on a corpus of press articles, and to analyse the initial consequences of these politicisations on public action and the practices of cruise ship owners.